PENERAPAN ACCESS CONTROL LIST (ACL) DALAM PENGAMANAN JARINGAN KOMPUTER - Rakhmadi Rahman; Meyrani R; Wahyu Anwar (Jurnal Riset Sistem Informasi, 2026)
Computer networks supporting organizational operations are increasingly vulnerable to unauthorized access as connectivity grows. This study aims to analyze the effectiveness of Access Control List implementation in securing computer networks through a segmented network simulation approach. A simulated network environment was constructed to evaluate the ability of ACL to distinguish between permitted and unauthorized traffic. The results indicate that ACL successfully blocks unauthorized access while maintaining legitimate network services. These findings confirm that ACL remains an effective basic access control mechanism in controlled network environments.